Effect of Bonding Time and Bonding Temperature on Lead-Free Solder Joints Dispersed Pillar Shaped IMCs. (2017) - Hayashi, Yawara; Nakata, Yusuke; Shohji, Ikuo; Koyama, Shinji; Hashimoto, Tomihito
Abstract: The effects of the bonding time and temperature on microstructures and the joint strength of solder joints dispersed pillar shaped intermetallic compounds (IMCs) with Sn-3.0Ag-0.5Cu (mass%, SAC) and Sn-3.0Ag-0.7Cu-5.0In (mass%, SACI) alloys were investigated. The effects of the electrode type and the joint height on them were also investigated. In the Cu/Cu joint with SAC, the length of the pillar shaped IMC increased with increasing the bonding time although the effect of the bonding temperature on it was negligible. The thick joint height was effective to form pillar shaped IMCs in the joint. In the Cu/Ni joint with SAC, thin pillar shaped IMCs formed in the joint. In the joints with SACI, the high bonding temperature was effective to generate a large quantity of pillar shaped IMCs regardless of the electrode type. The small amount of In addition is effective to increase the nucleation site of the primary IMC and the thick joint height is effective to form finer pillar shaped IMCs in the joint. The die shear force measurement revealed that the pillar shape IMC such as to connect both sides is effective to improve the joint strength.